(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article discusses the relationship between written literature and folklore. Written literature and folklore cannot be imagined without each other. Motive stylization can be found not only in epic works, but also in children’s game folklore. Children’s folklore is usually created within epic traditions. For this reason, the motifs in it are colorful and similar to epic works. The composition of folklore works should be studied through the analysis of motifs. Such motifs as honesty, test, journey, rescue, danger, death, resurrection, captivity, bargaining, flight, adoption, wish for goodness, shame, punishment are more common in children’s game folklore.